Successful Treatment of Holmes Tremor With Deep Brain Stimulation of the Prelemniscal Radiations - Martinez, Vicente; Hu, Shu-Ching; Foutz, Thomas J.; Ko, Andew (Frontiers in Surgery, 2018)
Holmes tremor (HT) is a rare movement disorder that is typically associated with cerebellar, thalamic or brainstem lesions following a delay. Treatment of HT with deep brain stimulation (DBS) has yielded positive results however; it is unclear which deep brain targets provide optimal therapeutic effects. Here we describe a case report in which a 34 year old man with HT treated successfully with DBS. The ventrointermediate nucleus (VIM) of the thalamus was considered as the initial target. Following electrode placement we determined that the ventral-most electrode contacts were located in the prelemniscal radiations (Raprl). When stimulating from the Raprl contacts, the patient demonstrated robust, stable therapeutic improvements using remarkably low voltages. Our case report corroborates prior evidence suggesting the Raprl as a viable therapeutic target for treating HT with DBS.